Gender Comparison of Severity of Pain, Stiffness, And Functional Limitation Among Second Stage Knee Osteoarthritis Patients with Diabetes: Gender Comparison of Osteoarthritis Patients with Diabetes - Raza Khan, Haroon; Ruksar, Safina; Haq, Kiran; Asif, Somiya; Ratan Kumar, Priyanka; Sharif, Zarqa; Faizan Hamid, Muhammad; Muhammad Arslan, Hafiz Rana (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Osteoarthritis (OA) and diabetes mellitus (DM) are two medical conditions that frequently exist together and cause poor consequences. OA is described as joint pain and is one of the main reasons for impairment. Diabetes is high levels of glucose in blood because of disruption in insulin metabolism. Objective: To compare gender variations of severity of pain, stiffness and difficulty in functional performance among patients of second stage knee OA with diabetes. Methods: Data were collected from 360 individuals with mean age 52.32 ± 4.989 years for males and 50.73 ± 4.763 years for females. Individuals with definite osteophytes in knee joint and clinically diagnosed DM were included in the study. The severity of stiffness and functional limitation was calculated using WOMAC questionnaire. Results: The mean of pain score was 9.0833 ± 3.04322, stiffness score was 4.3389 ± 1.12446 and the mean of physical function score was 34.0944 ± 8.65135. Overall, 109 patients had less severe symptoms while 71 had more severe symptoms. Among 180 female participants, n=15 had mild, n=139 had moderate and n=26 had severe pain on NPRS. The mean of the pain score was 9.8778 ± 2.90762. The mean of stiffness score was 4.5167 ± 1.28365 and the mean of physical function score was 37.1611 ± 7.98963. Conclusion: Our findings concluded that the gender difference of severity of pain and physical function limitation was statistically significant, but no significant difference was found in severity of stiffness. Also, females with diabetes had more severe symptoms than males with diabetes